2022
DOI: 10.3390/ijerph192114004
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Research Studies Addressing Patient-Practitioner Communication about Online Health Information

Abstract: Modern healthcare is becoming increasingly technologized, knowledge-intensive, and specialized, which has consequences for communication between patients andpractitioners in clinical encounters. Health information is increasingly accessible to patients through online resources . The objective of this paper is to provide an overview of existing studies that address how patients communicate with practitioners about online health information and to identify the key topics raised in these studies. With the concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our findings showed that socioeconomically disadvantaged people turn to the internet as a compensatory strategy, mainly to find self-treatment solutions or inexpensive home remedies. As such, it reflects the poor access to healthcare of people with a precarious or disadvantaged socioeconomic status in the Swiss context, due to the financial difficulties and a poorly developed primary healthcare system in Switzerland [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that socioeconomically disadvantaged people turn to the internet as a compensatory strategy, mainly to find self-treatment solutions or inexpensive home remedies. As such, it reflects the poor access to healthcare of people with a precarious or disadvantaged socioeconomic status in the Swiss context, due to the financial difficulties and a poorly developed primary healthcare system in Switzerland [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women are more likely to use the internet for searching health information than men [93], and have thus a better knowledge of online health resources. Fifthly, the age range of the sample is rather narrow (age range [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. This can be explained by the recruitment sites chosen, which are specifically PLOS ONE aimed at the working population.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…A more conventional study in the knowledge tradition of social health literacy research was offered by Larson and Gilstad (2022) [44]. Using a systematic review approach, Larson and Gilstad (2022) [44] analyzed qualitative studies focusing on how patients understand online health information and communicate their findings with healthcare professionals. Of the 16 studies included in their review, ten focused on the patient perspective, four addressed the provider perspective, and two articles included both perspectives.…”
Section: Health Literacy and Social Context Findings From The Special...mentioning
confidence: 99%